Freedom . Freedom through anarchism
Also subtitled: Anarchist fortnightly, Anarchist weekly, and Anarchist monthly. - For suppl. see: Freedom anarchist pamphlets (ZDK 40336). Till 69(2008):no.3 subtitled: anarchist news and views Suppl. titled: Freedom's anarchist review. Until 6(1945):no.21 titled :War commentary for anarchism (ZO 6958) and (ZF 40993)